Quasars as probes of cosmological reionization - Mortlock,D (Springer International Publishing, 2016)
Quasars are the most luminous non-transient sources in the epoch of cosmological reionization (which ended a billion years after the Big Bang, corresponding to a redshift of z  5), and are powerful probes of the inter-galactic medium at that time. This review covers current efforts to identify high-redshift quasars and how they have been used to constrain the reionization history. This includes a full description of the various processes by which neutral hydrogen atoms can absorb/scatter ultraviolet photons, and which lead to the Gunn-Peterson effect, dark gap and dark pixel analyses, quasar near zones and damping wing absorption. Finally, the future prospects for using quasars as probes of reionization are described.